Operative Treatment of Fifth Metatarsal Jones Fractures (Zones II and III) in the NBA. Issue 1 (19th August 2016) - O'Malley, Martin; DeSandis, Bridget A.; Allen, Answorth; Levitsky, Matthew M.; O'Malley, Quinn; Williams, Riley
Category: Sports. Introduction/Purpose: Proximal fractures (Zones II and III) of the fifth metatarsal are common in the elite athlete population with basketball players being especially prone to developing these injuries. Fractures in Zones II and III of the fifth metatarsal can be difficult to treat due to tendency toward delayed union, nonunion, or refracture. The purpose of this case series is to report our experience in treating 10 professional basketball players from the National Basketball Association (NBA) for proximal fifth metatarsal fractures and determine the healing rate, return to play, refracture rate and role of foot type in these athletes. Methods: The records of 10 professional basketball players who were treated for fifth metatarsal fractures between September 2008 and October 2014 were retrospectively reviewed. Seven athletes underwent standard percutaneous internal fixation with bone marrow aspirate concentrate (BMAC) while the other 3 had open bone grafting primarily in addition to fixation and BMAC. Radiographic features associated with recurrent fifth metatarsal fractures were reported including fourth-fifth intermetatarsal (IMA4-5), fifth metatarsal lateral deviation (MT5-LD), calcaneal pitch (CP), and metatarsus adductus (MAA) angles. Differences in clinical and radiographic features were assessed between athletes who refractured (n=3) and those who did not (n=7). Results: Radiographic healing was observed at an overall average of 7.5 weeks and return to play was 9.8 weeks. Three athletes experienced refractures. When comparing the refracture group (n=3) with the control group (n=7), there were no significant differences in clinical features or radiographic measurements except that the refracture group had the highest measured MAA. Four of 10 fit the criteria for having metatarsus adductus as measured by the Sgarlato method (MAA greater than 14 degrees) while 5 of 10 had metatarsus adductus using the Engel method (greater than 24 degrees). All refractures had an abnormal angle using the Engel method. Seven of the 10 athletes were classified as pes planus and 9/10 had a bony prominence under the proximal base of their fifth metatarsals styloid. Conclusion: This is the largest series of operatively treated professional basketball players that possess a unique foot type that seems to be associated with increased risk of fifth metatarsal fracture and refracture. This foot type is one which has forefoot metatarsus adductus and a fifth metatarsal that is curved with a prominent base. We continue to use standard internal fixation with bone marrow aspirate but advocate additional prophylactic open bone grafting in patients with high IMA4-5, MT5-LD and MAA angles as well as prominent fifth metatarsal styloids in order to improve fracture healing and potentially decrease the risk of refracture.